Dab2 stabilizes Axin and attenuates Wnt/β-catenin signaling by preventing protein phosphatase 1 (PP1)–Axin interactions - Jiang, Y (2009)
Wnt/β-catenin signaling plays a pivotal role in modulating cellular proliferation, differentiation, tissue organization and embryonic development. Earlier, we found that the endocytic adaptor disabled-2 (Dab2) could attenuate Wnt/β-catenin signaling by stabilizing Axin and preventing its translocation to the membrane. Recently, protein phosphatase 1 (PP1) has been shown to interact with, and dephosphorylate Axin, leading to its destabilization. Here, we show that Dab2 functions upstream of PP1 to block the interaction between Axin and PP1, inhibiting Axin dephosphorylation and thereby stabilizing its expression, ultimately leading to inhibition of Wnt/β-catenin. We show that Dab2 acts as a competitive inhibitor of PP1 by binding to the same C-terminal domain of Axin. Both PP1 and Axin bind to the N-terminus of Dab2 and a Dab2 truncation mutant consisting of the N-terminal phosphotyrosine binding domain blocks PP1–Axin interactions and inhibits Wnt signaling. We confirm the inhibitory effect of Dab2 on Wnt/β-catenin signaling in zebrafish embryos, showing that its ectopic expression phenocopies Axin overexpression resulting in altered dorsoventral patterning. We conclude that Dab2 stabilizes Axin and attenuates Wnt/β-catenin signaling by preventing PP1 from binding Axin.